858. Inter-rater Reliability of Hand Hygiene Observers with an Electronic Monitoring System. (31st December 2020) - Bailey, Pamela; Armstrong-Novak, Jo Dee; Cooper, Kaila; Stevens, Michael; Bearman, Gonzalo; Doll, Michelle
Abstract: Background: Hand hygiene (HH) is the bedrock of infection prevention. Knowing the limitations of hand hygiene observers, Virginia Commonwealth University Health System invested in technology to remotely monitor health care workers's (HCW) HH. Each hand sanitizer and soap dispenser in the patient care areas has a sensor, as well as each patient's bed and each HCW. As the HCW moves around the environment, the sensors detect whether or not HH was performed for each opportunity. Methods: While monitoring HH via observations, we compared the manual observations and the technologic hand hygiene observations. Results: Of 31 witnessed and manually recorded HH observations, 30 were noted in the electronic system (96.7% correspondence). There was only one witnessed opportunity that the technology failed to capture, when the staff member was performing hand hygiene while standing in the doorway talking to the nurse inside the room. There were multiple missed opportunities for HH while in patient rooms, as defined by the WHO's Five Moments. Conclusion: There was excellent correspondence between the manual observations and the HH technology in this study. There is significant limitation in what an observer can do, while the HH technology will average around 35, 000 'observations' on a daily basis and is capable of capturing more of the 5 moments of HH. We have previously noted interference in the wireless technology in the healthcare environment. However, failure of providers to perform HH when indicated overshadow the failures of technology to capture HH that is performed. Better understanding of the indications for HH in accordance with the WHO 5 Moments may improve provider trust in the technology. Disclosures: All Authors : No reported disclosures